A 21‐Locus Autosomal SNP Multiplex and its Application in Forensic Science1. Issue 1 (29th October 2013) - Hou, Guangwei; Jiang, Xianhua; Yang, Yanyan; Jia, Fei; Li, Qiang; Zhao, Jinling; Guo, Fei; Liu, Limin
Abstract To develop a cost‐effective technique for single‐nucleotide polymorphism (SNP) genotyping and improve the efficiency to analyze degraded DNA, we have established a novel multiplex system including 21‐locus autosomal SNPs and amelogenin locus, which was based on allele‐specific amplification (ASA) and universal reporter primers (URP). The target amplicons for each of the 21 SNPs arranged from 63 base pair (bp) to 192 bp. The system was tested in 539 samples from three ethnic groups (Han, Mongolian, and Zhuang population) in China, and the total power of discrimination (TPD) and cumulative probability of exclusion (CPE) were more than 0.99999999 and 0.98, respectively. The system was further validated with forensic samples and full profiles could be achieved from degraded DNA and 63 case‐type samples. In summary, the multiplex system offers an effective technique for individual identification of forensic samples and is much more efficient in the analysis of degraded DNA compared with standard STR typing.